Plain and metrizamide CT of lumbar disk disease: comparison with myelography. - Anand, A K; Lee, B C (American Journal of Neuroradiology, 1982)
Computed tomography with and without administration of intrathecal contrast material was evaluated in 100 patients with suspected lumbar disk disease. Metrizamide computed tomography was performed in 75 patients and plain computed tomography was performed in 25. Metrizamide computed tomography was more accurate than plain computed tomography. It also disclosed many lesions not shown by metrizamide myelography at the lumbosacral level. Very few lesions were revealed by myelography that were not seen by metrizamide computed tomography. The small amount of intrathecal metrizamide needed for scanning has practically no side effects. Experience in 12 patients indicates that the procedure may be performed safely on an outpatient basis. This study suggests that computed tomography should be given serious consideration as the primary definitive radiographic examination of suspected lumbar disk disease.